Undressing a collective intersubband excitation in a quantum well - Craig, K.; Galdrikian, B.; Heyman, J. N.; Markelz, A. G.; Williams, J. B.; Sherwin, M. S.; Campman, K.; Hopkins, P. F.; Gossard, A. C. (Physical Review Letters, 1996)
We have experimentally measured the 1-2 intersubband absorption in a single 40 nm wide modulation-doped Al0.3Ga0.7As/GaAs square quantum well as a function of frequency, intensity, and charge density. The low-intensity depolarization-shifted absorption occurs near 80 cm(-1) (10 meV or 2.4 THz), nearly 30% higher than the intersubband spacing. At higher intensities, the absorption peak shifts to lower frequencies. Our data are in good agreement with a theory proposed by Zaluzny, which attributes the redshift to a reduction in the depolarization shift as the excited subband becomes populated.